Avatars of the historical distinction between historical writing and fictional writing - Silva Rodríguez, Manuel (Íkala, Revista de Lenguaje y Cultura, 2013)
<!-- [if gte mso 9]> Normal 0 21 false false false ES-MX X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES-MX X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES-MX X-NONE X-NONE <![endif]--> This article identifies how from their textual properties and from the pragmatic dimension of language the historical and the fictional have distanced and again found in cultural production. The text synthesizes and relates conceptual elements that have been exposed as constituting two modes of discursive production: the fictional writing and the historical writing. The text addresses issues such as the alleged distinction between history and fiction, the overlap in the use of textual and rhetorical resources and the boundary of the two domains in accordance with the covenants of reading that they have developed historically. The text aims to highlight that concepts like verisimilitude, veracity, narrative, subjectivity and relationship sign-historical order have been taken as criteria approach and differentiation between the two. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->